Synthesis and thermal properties of poly(ethylene glycol)-polydimetylsiloxane crosslinked copolymers - Ain Athirah Zainuddin; Rizafizah Othaman; Wan Syaidatul Aqma Wan Mohd Noor; Takeno Akiyoshi; Takahashi Shinya; Farah Hannan Anuar (Penerbit Universiti Kebangsaan Malaysia, 2018)
Poly(ethylene glycol)-polydimethylsiloxane (PEG-PDMS) crosslinked copolymers with mol ratios PEG:PDMS:Glycerol of 5:3:2, 6:2:2 and 7:1:2 have been prepared and characterized. The synthesis of the copolymers was carried out by the reaction between hydroxyl groups of PEG, PDMS and glycerol with isocyanate groups of 1,6-hexamethyelene diisocyanate (HMDI). In the reaction, glycerol was acted as the cross linker. The copolymers were then characterized by FTIR spectroscopy. The thermal behaviour was investigated by DSC and TGA. Based on FTIR results, the crosslinked structure of the copolymers was confirmed by the presence of absorption peak at 3350 and 1710 cm-1 which indicated the (-N-H) stretching and carbonyl (-C=O) correspond to urethane links. This showed that the hydroxyl groups of PEG, PDMS and glycerol have reacted to isocyanate groups of HMDI. The copolymers showed melting temperature (Tm) of PEG segments from 22°C to 27°C and glass transition temperature (Tg) from -11°C to -6°C. Meanwhile, the PDMS segment showed values from -53°C to -56°C for Tm, and Tg from -118°C to -122°C. Data obtained from the thermal analysis indicate that thermal stability increases with increasing PDMS mol ratio.